Realization of a computed tomography setup to achieve resolutions below 1μm - Salamon, M.; Hanke, R.; Krueger, P.; Uhlmann, Norman; Voland, V. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2008)
The amelioration of present X-ray imaging systems especially in computed tomography to resolutions below 1 extgreekmm necessitates very precise equipment details such as the manipulators, focus size and stability of the tube and the detector adjustment. In this paper, we present an experimental setup of a computed tomography system with sub-micrometer resolution. The requirements on and characteristics of the components and their influence on the measurements are discussed and exemplary results of different test objects in the field of non-destructive testing with sub-micrometer resolution are presented.
EAM Import::2019-03-13